A high-toughness braided ceramic material and preparation method
By optimizing the raw material combination of braided ceramic materials and adding modified carbon nanotube polyphonic dopant and intercalation supplements, the problems of durability and stability of braided ceramic materials are solved, and the fracture toughness, scrubbing and corrosion resistance of the product are significantly improved.
Patent Information
- Application Number
- CN202411848475.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-16
AI Technical Summary
The existing woven ceramic materials have poor durability and insufficient fracture toughness, scrubbing resistance and corrosion resistance, which affects the product's applicable life and efficiency.
Raw materials such as diopside, quartz, silicon carbide, boron nitride and alumina are used, and the interface activity of sodium dodecyl benzene sulfonate solution is improved, and the dopant additives for polybuting of modified carbon nanotubes and co-supplementing of interlayers are added to optimize the harmony and coordination between the raw materials and enhance the performance of the product.
It significantly improves the fracture toughness, scrubbing and corrosion resistance of woven ceramic materials, extends the product's applicable life and improves the use efficiency.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramics, and in particular to a high-toughness braided ceramic material and a preparation method thereof. Background Art
[0002] The woven ceramic material is a kind of ceramic. The clay is made into thin strips and then woven into various shapes. The woven ceramic material is made by impregnating carbon fiber and basalt skeleton into the ceramic material and then weaving it. However, the existing woven ceramic material has poor durability and poor fracture toughness, scrub resistance and corrosion resistance, which affects the service life of the product and limits the use efficiency of the product. Based on this, the present invention further improves it. Summary of the invention
[0003] In view of the defects of the prior art, the object of the present invention is to provide a high-toughness braided ceramic material and a preparation method to solve the problems raised in the above background technology.
[0004] The present invention solves the technical problem by adopting the following technical solution:
[0005] The present invention provides a high-toughness braided ceramic material, comprising the following raw materials in parts by weight:
[0006] 30-40 parts of diopside, 20-30 parts of quartz, 10-15 parts of silicon carbide, 7-11 parts of boron nitride, 6-10 parts of modified carbon nanotube polyadmixture additive, 5-7 parts of intercalation synergist, 4-6 parts of aluminum oxide, 10-15 parts of water, and 3-5 parts of sodium dodecylbenzene sulfonate solution.
[0007] Preferably, the high-toughness braided ceramic material comprises the following raw materials in parts by weight:
[0008] 37.5 parts of diopside, 25 parts of quartz, 12.5 parts of silicon carbide, 9 parts of boron nitride, 8 parts of modified carbon nanotube polyadmixture additive, 6 parts of intercalation synergist, 5 parts of aluminum oxide, 12.5 parts of water, and 4 parts of sodium dodecylbenzene sulfonate solution.
[0009] Preferably, the mass fraction of the sodium dodecylbenzene sulfonate solution is 2-5%.
[0010] Preferably, the preparation method of the modified carbon nanotube polyadmixture additive is:
[0011] S01: placing the carbon nanotubes in a proton irradiation box for 10-15 minutes, with an irradiation power of 350-400W. After the irradiation is completed, ultrasonic treatment is performed in a sufficient amount of hydrochloric acid solution, with an ultrasonic power of 450-500W for 1 hour. After the ultrasonic treatment is completed, the carbon nanotubes are washed with water, filtered, and dried to obtain pretreated carbon nanotubes;
[0012] S02: Add 2-5 parts of nano calcium carbonate and 1-3 parts of nano silica sol to 5-8 parts of lanthanum chloride solution by weight, then add 2-4 parts of yttrium oxide and 1-2 parts of aluminum borate whisker, stir well, and obtain a polyadjusted doping solution;
[0013] S03: ball-milling the pretreated carbon nanotubes and the compounding doping liquid at a weight ratio of 5:3. After the ball-milling is completed, washing and drying are performed to obtain a modified carbon nanotube compounding doping agent.
[0014] Preferably, the mass fraction of the hydrochloric acid solution is 2-4%; the mass fraction of the lanthanum chloride solution is 3-6%; the ball milling speed in S03 is 1000-1300 r / min, and the ball milling is 2h.
[0015] Preferably, the preparation method of the intercalated synergist is:
[0016] S101: adding 4 to 6 parts of flaky talc and 1 to 2 parts of silane coupling agent KH550 to 6 to 10 parts of chitosan solution by weight, and then adding 2 to 3 parts of carboxymethyl cellulose, stirring well, to obtain a modifier;
[0017] S102: stirring hydroxyapatite in a sufficient amount of 5% by mass sodium alginate solution to obtain hydroxyapatite liquid;
[0018] Add 4 to 7 parts of a modifier by weight to 10 to 15 parts of a hydroxyapatite liquid, and then perform ultrasonic treatment until the ultrasonic treatment is terminated to obtain a modified liquid doped with hydroxyapatite;
[0019] S103: The modified liquid mixed with hydroxyapatite and the intercalation agent are mixed in a weight ratio of 3:5, and the mixture is ball-milled at a speed of 1500 r / min for 1 h. After the ball-milling is completed, the mixture is filtered and dried to obtain the intercalation synergistic agent.
[0020] Preferably, the mass fraction of the chitosan solution is 2-5%; the ultrasonic power of the ultrasonic treatment is 450-500 W, and the ultrasonic time is 30-40 min.
[0021] Preferably, the preparation method of the intercalant is:
[0022] The nano-bentonite is heat-treated at 230-240°C for 10-20 minutes, and then stirred and dispersed evenly in water at 5°C, and then filtered and dried to obtain the pre-treated nano-bentonite;
[0023] According to weight, 4-7 parts of pretreated nano bentonite and 1-3 parts of nano magnesium oxide are added to 5-8 parts of barium nitrate solution, and then 1-2 parts of nano titanium dioxide and 2-3 parts of sodium lignin sulfonate solution are added, stirred, filtered and dried after the treatment is completed to obtain an intercalation agent.
[0024] Preferably, the mass fraction of the barium nitrate solution is 2-4%; the mass fraction of the sodium lignin sulfonate solution is 4-7%; the stirring speed of the stirring treatment is 450-550 r / min, and the stirring time is 30-40 min.
[0025] The present invention also provides a method for preparing a high-toughness woven ceramic material, which is used to prepare the high-toughness woven ceramic material, comprising the following steps:
[0026] Diopside, quartz, silicon carbide, boron nitride, modified carbon nanotube compound additives, intercalation synergist, alumina, water and sodium dodecylbenzene sulfonate solution are mixed and ball-milled at a ball-milling speed of 1000 r / min for 2 hours to obtain a high-toughness woven ceramic material.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] The high-toughness braided ceramic material of the present invention adopts diopside in combination with quartz, silicon carbide, boron nitride and alumina raw materials, and the interfacial activity of the sodium dodecylbenzene sulfonate solution is improved to optimize the coordination effect between the raw materials. At the same time, the modified carbon nanotube compounding additive and the intercalation synergist are added to coordinate and enhance the durability of the product. The product has excellent fracture toughness, and has significant scrub resistance and corrosion resistance stability, and the product has significant performance improvement effect.
[0029] The modified carbon nanotube compounding additive adopts carbon nanotubes that have been irradiated with protons and then treated with hydrochloric acid to optimize the activity performance of the carbon nanotubes. At the same time, the compounding doping liquid is improved by ball milling. The compounding doping liquid is coordinated with nano calcium carbonate, nano silica sol, lanthanum chloride solution, yttrium oxide and aluminum borate whiskers. The high surface area of the carbon nanotubes is used for carrying, and the nano calcium carbonate and aluminum borate whiskers are used for coordination. The co-coordination between the raw materials is used to optimize the interface of the raw materials, and the effect of the carbon nanotubes carrying the nano calcium carbonate and aluminum borate whiskers is improved, thereby strengthening the system performance and optimizing the product performance stability;
[0030] The intercalation synergist is prepared by ball milling with a modified liquid mixed with hydroxyapatite and an intercalation agent. The intercalation agent is heat-treated with nano-bentonite at 230-240°C for 10-20 minutes, and then stirred and dispersed evenly in water at 5°C, and then filtered and dried to optimize the dispersion and interlayer spacing of the nano-bentonite. At the same time, nano-magnesium oxide, barium nitrate solution, nano-titanium dioxide and sodium lignin sulfonate solution are combined to strengthen the intercalation interlayer spacing of the nano-bentonite through the coordination and matching of the raw materials, so as to facilitate the nano-bentonite to be intercalated in the system. , enhance the performance stability of the system, and at the same time, the modified liquid mixed with hydroxyapatite adopts hydroxyapatite to be formulated into sodium alginate solution to improve the dispersion of hydroxyapatite. At the same time, flaky talcum powder is used as the matrix material, and the modifier is blended with silane coupling agent KH550, chitosan solution and carboxymethyl cellulose. Flaky talcum powder is used as the flaky structure to be interspersed into the sheet layer, and then the hydroxyapatite at the blending point is returned, and then the intercalated synergist is assembled in the system to further enhance the fracture toughness of the product, as well as the scrub resistance and corrosion resistance stability. The effect is remarkable. DETAILED DESCRIPTION
[0031] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] A high-toughness braided ceramic material of this embodiment includes the following raw materials in parts by weight:
[0033] 30-40 parts of diopside, 20-30 parts of quartz, 10-15 parts of silicon carbide, 7-11 parts of boron nitride, 6-10 parts of modified carbon nanotube polyadmixture additive, 5-7 parts of intercalation synergist, 4-6 parts of aluminum oxide, 10-15 parts of water, and 3-5 parts of sodium dodecylbenzene sulfonate solution.
[0034] The mass fraction of the sodium dodecylbenzene sulfonate solution of the present embodiment is 2-5%.
[0035] The preparation method of the modified carbon nanotube polyadjusting additive of this embodiment is:
[0036] S01: placing the carbon nanotubes in a proton irradiation box for 10-15 minutes, with an irradiation power of 350-400W. After the irradiation is completed, ultrasonic treatment is performed in a sufficient amount of hydrochloric acid solution, with an ultrasonic power of 450-500W for 1 hour. After the ultrasonic treatment is completed, the carbon nanotubes are washed with water, filtered, and dried to obtain pretreated carbon nanotubes;
[0037] S02: Add 2-5 parts of nano calcium carbonate and 1-3 parts of nano silica sol to 5-8 parts of lanthanum chloride solution by weight, then add 2-4 parts of yttrium oxide and 1-2 parts of aluminum borate whisker, stir well, and obtain a polyadjusted doping solution;
[0038] S03: ball-milling the pretreated carbon nanotubes and the compounding doping liquid at a weight ratio of 5:3. After the ball-milling is completed, washing and drying are performed to obtain a modified carbon nanotube compounding doping agent.
[0039] The mass fraction of the hydrochloric acid solution in this embodiment is 2-4%; the mass fraction of the lanthanum chloride solution is 3-6%; the ball milling speed in S03 is 1000-1300 r / min, and the ball milling is 2h.
[0040] The preparation method of the intercalation synergist of this embodiment is as follows:
[0041] S101: adding 4 to 6 parts of flaky talc and 1 to 2 parts of silane coupling agent KH550 to 6 to 10 parts of chitosan solution by weight, and then adding 2 to 3 parts of carboxymethyl cellulose, stirring well, to obtain a modifier;
[0042] S102: stirring hydroxyapatite in a sufficient amount of 5% by mass sodium alginate solution to obtain hydroxyapatite liquid;
[0043] Add 4 to 7 parts of a modifier by weight to 10 to 15 parts of a hydroxyapatite liquid, and then perform ultrasonic treatment until the ultrasonic treatment is terminated to obtain a modified liquid doped with hydroxyapatite;
[0044] S103: The modified liquid mixed with hydroxyapatite and the intercalation agent are mixed in a weight ratio of 3:5, and the mixture is ball-milled at a speed of 1500 r / min for 1 h. After the ball-milling is completed, the mixture is filtered and dried to obtain the intercalation synergistic agent.
[0045] The mass fraction of the chitosan solution in this embodiment is 2-5%; the ultrasonic power of the ultrasonic treatment is 450-500W, and the ultrasonic time is 30-40min.
[0046] The preparation method of the intercalant of this embodiment is:
[0047] The nano-bentonite is heat-treated at 230-240°C for 10-20 minutes, then stirred and dispersed evenly in water at 5°C, then filtered and dried to obtain pre-treated nano-bentonite;
[0048] According to weight, 4-7 parts of pretreated nano bentonite and 1-3 parts of nano magnesium oxide are added to 5-8 parts of barium nitrate solution, and then 1-2 parts of nano titanium dioxide and 2-3 parts of sodium lignin sulfonate solution are added, stirred, filtered and dried after the treatment is completed to obtain an intercalation agent.
[0049] The mass fraction of the barium nitrate solution in this embodiment is 2-4%; the mass fraction of the sodium lignin sulfonate solution is 4-7%; the stirring speed of the stirring treatment is 450-550 r / min, and the stirring time is 30-40 min.
[0050] A method for preparing a high-toughness braided ceramic material of this embodiment includes the following steps:
[0051] Diopside, quartz, silicon carbide, boron nitride, modified carbon nanotube compound additives, intercalation synergist, alumina, water and sodium dodecylbenzene sulfonate solution are mixed and ball-milled at a ball-milling speed of 1000 r / min for 2 hours to obtain a high-toughness woven ceramic material.
[0052] A high-toughness braided ceramic body of this embodiment includes the following steps:
[0053] According to weight, 20 parts of high-toughness woven ceramic material are weighed, and then 5 parts of organic boron crosslinking agent CY-2, 3 parts of aluminum sol and 3 parts of polyacrylic acid are mixed and continued to be ball-milled to obtain ball-milled material; then carbon fiber and basalt fiber are fully impregnated into the ball-milled material, and after the impregnation is completed, impregnated carbon fiber and impregnated carbon fiber are obtained; then the impregnated carbon fiber and the impregnated carbon fiber are three-dimensionally orthogonally woven, and after the weaving is completed, they are dried at 150°C to obtain a dry woven ceramic blank; finally, the dried woven ceramic blank is sintered at 800°C for 2.5 hours to obtain a high-toughness woven ceramic body.
[0054] Embodiment 1: A high-toughness braided ceramic material, comprising the following raw materials in parts by weight:
[0055] 30 parts of diopside, 20 parts of quartz, 10 parts of silicon carbide, 7 parts of boron nitride, 6 parts of modified carbon nanotube polyadmixture additive, 5 parts of intercalation synergist, 4 parts of aluminum oxide, 10 parts of water, and 3 parts of sodium dodecylbenzene sulfonate solution.
[0056] The mass fraction of the sodium dodecylbenzenesulfonate solution of the present embodiment is 2%.
[0057] The preparation method of the modified carbon nanotube polyadjusting additive of this embodiment is:
[0058] S01: placing the carbon nanotubes in a proton irradiation box for 10 minutes at an irradiation power of 350W, and then ultrasonicating them in a sufficient amount of hydrochloric acid solution at an ultrasonic power of 450W for 1 hour, and then washing, filtering, and drying to obtain pretreated carbon nanotubes;
[0059] S02: Add 2 parts of nano calcium carbonate and 1 part of nano silica sol to 5 parts of lanthanum chloride solution by weight, then add 2 parts of yttrium oxide and 1 part of aluminum borate whisker, stir well, and obtain a polyadjusted doping solution;
[0060] S03: ball-milling the pretreated carbon nanotubes and the compounding doping liquid at a weight ratio of 5:3. After the ball-milling is completed, washing and drying are performed to obtain a modified carbon nanotube compounding doping agent.
[0061] The mass fraction of the hydrochloric acid solution in this embodiment is 2%; the mass fraction of the lanthanum chloride solution is 3%; the ball milling speed in S03 is 1000r / min, and the ball milling is 2h.
[0062] The preparation method of the intercalation synergist of this embodiment is as follows:
[0063] S101: adding 4 parts of flaky talc and 1 part of silane coupling agent KH550 to 6 parts of chitosan solution by weight, and then adding 2 parts of carboxymethyl cellulose, stirring well, to obtain a modifier;
[0064] S102: stirring hydroxyapatite in a sufficient amount of 5% by mass sodium alginate solution to obtain hydroxyapatite liquid;
[0065] Adding 4 parts of a modifier to 10 parts of a hydroxyapatite liquid by weight, followed by ultrasonic treatment, and ending the ultrasonic treatment to obtain a modified liquid doped with hydroxyapatite;
[0066] S103: The modified liquid mixed with hydroxyapatite and the intercalation agent are mixed in a weight ratio of 3:5, and the mixture is ball-milled at a speed of 1500 r / min for 1 h. After the ball-milling is completed, the mixture is filtered and dried to obtain the intercalation synergistic agent.
[0067] The mass fraction of the chitosan solution in this embodiment is 2%; the ultrasonic power of the ultrasonic treatment is 450W, and the ultrasonic time is 30 minutes.
[0068] The preparation method of the intercalant of this embodiment is:
[0069] The nano-bentonite is heat-treated at 230°C for 10 minutes, then stirred and dispersed evenly in water at 5°C, then filtered and dried to obtain pretreated nano-bentonite;
[0070] According to weight, 4 parts of pretreated nano bentonite and 1 part of nano magnesium oxide are added to 5 parts of barium nitrate solution, and then 1 part of nano titanium dioxide and 2 parts of sodium lignin sulfonate solution are added, stirred, filtered and dried after the treatment is completed to obtain an intercalation agent.
[0071] The mass fraction of the barium nitrate solution in this embodiment is 2%; the mass fraction of the sodium lignin sulfonate solution is 4%; the stirring speed of the stirring process is 450 r / min, and the stirring time is 30 min.
[0072] A method for preparing a high-toughness braided ceramic material of this embodiment includes the following steps:
[0073] Diopside, quartz, silicon carbide, boron nitride, modified carbon nanotube compound additives, intercalation synergist, alumina, water and sodium dodecylbenzene sulfonate solution are mixed and ball-milled at a ball-milling speed of 1000 r / min for 2 hours to obtain a high-toughness woven ceramic material.
[0074] A high-toughness braided ceramic body of this embodiment includes the following steps:
[0075] According to weight, 20 parts of high-toughness woven ceramic material are weighed, and then 5 parts of organic boron crosslinking agent CY-2, 3 parts of aluminum sol and 3 parts of polyacrylic acid are mixed and continued to be ball-milled to obtain ball-milled material; then carbon fiber and basalt fiber are fully impregnated into the ball-milled material, and after the impregnation is completed, impregnated carbon fiber and impregnated carbon fiber are obtained; then the impregnated carbon fiber and the impregnated carbon fiber are three-dimensionally orthogonally woven, and after the weaving is completed, they are dried at 150°C to obtain a dry woven ceramic blank; finally, the dried woven ceramic blank is sintered at 800°C for 2.5 hours to obtain a high-toughness woven ceramic body.
[0076] Embodiment 2: A high-toughness braided ceramic material, comprising the following raw materials in parts by weight:
[0077] 40 parts of diopside, 30 parts of quartz, 15 parts of silicon carbide, 11 parts of boron nitride, 10 parts of modified carbon nanotube polyadmixture additive, 7 parts of intercalation synergist, 6 parts of aluminum oxide, 15 parts of water, and 5 parts of sodium dodecylbenzene sulfonate solution.
[0078] The mass fraction of the sodium dodecylbenzenesulfonate solution of the present embodiment is 5%.
[0079] The preparation method of the modified carbon nanotube polyadjusting additive of this embodiment is:
[0080] S01: placing the carbon nanotubes in a proton irradiation box for 15 minutes at a power of 400W, and then ultrasonicating them in a sufficient amount of hydrochloric acid solution at a power of 500W for 1 hour, and then washing, filtering, and drying to obtain pretreated carbon nanotubes;
[0081] S02: Add 5 parts of nano calcium carbonate and 3 parts of nano silica sol to 8 parts of lanthanum chloride solution by weight, then add 4 parts of yttrium oxide and 2 parts of aluminum borate whiskers, stir well, and obtain a polyadjusted doping solution;
[0082] S03: ball-milling the pretreated carbon nanotubes and the compounding doping liquid at a weight ratio of 5:3. After the ball-milling is completed, washing and drying are performed to obtain a modified carbon nanotube compounding doping agent.
[0083] The mass fraction of the hydrochloric acid solution in this embodiment is 4%; the mass fraction of the lanthanum chloride solution is 6%; the ball milling speed in S03 is 1300r / min, and the ball milling is 2h.
[0084] The preparation method of the intercalation synergist of this embodiment is as follows:
[0085] S101: adding 6 parts of flaky talc and 2 parts of silane coupling agent KH550 to 10 parts of chitosan solution by weight, and then adding 3 parts of carboxymethyl cellulose, stirring well, to obtain a modifier;
[0086] S102: stirring hydroxyapatite in a sufficient amount of 5% by mass sodium alginate solution to obtain hydroxyapatite liquid;
[0087] 7 parts of a modifier are added to 15 parts of a hydroxyapatite liquid by weight, followed by ultrasonic treatment, and the ultrasonic treatment is terminated to obtain a modified liquid doped with hydroxyapatite;
[0088] S103: The modified liquid mixed with hydroxyapatite and the intercalation agent are mixed in a weight ratio of 3:5, and the mixture is ball-milled at a speed of 1500 r / min for 1 h. After the ball-milling is completed, the mixture is filtered and dried to obtain the intercalation synergistic agent.
[0089] The mass fraction of the chitosan solution in this embodiment is 5%; the ultrasonic power of the ultrasonic treatment is 500 W, and the ultrasonic time is 40 min.
[0090] The preparation method of the intercalant of this embodiment is:
[0091] The nano-bentonite is heat-treated at 240°C for 20 minutes, then stirred and dispersed evenly in water at 5°C, then filtered and dried to obtain pretreated nano-bentonite;
[0092] According to weight, 7 parts of pretreated nano bentonite and 3 parts of nano magnesium oxide are added to 8 parts of barium nitrate solution, and then 2 parts of nano titanium dioxide and 3 parts of sodium lignin sulfonate solution are added, stirred, filtered and dried to obtain an intercalation agent.
[0093] The mass fraction of the barium nitrate solution in this embodiment is 4%; the mass fraction of the sodium lignin sulfonate solution is 7%; the stirring speed of the stirring process is 550 r / min, and the stirring time is 40 min.
[0094] A method for preparing a high-toughness braided ceramic material of this embodiment includes the following steps:
[0095] Diopside, quartz, silicon carbide, boron nitride, modified carbon nanotube compound additives, intercalation synergist, alumina, water and sodium dodecylbenzene sulfonate solution are mixed and ball-milled at a ball-milling speed of 1000 r / min for 2 hours to obtain a high-toughness woven ceramic material.
[0096] A high-toughness braided ceramic body of this embodiment includes the following steps:
[0097] According to weight, 20 parts of high-toughness woven ceramic material are weighed, and then 5 parts of organic boron crosslinking agent CY-2, 3 parts of aluminum sol and 3 parts of polyacrylic acid are mixed and continued to be ball-milled to obtain ball-milled material; then carbon fiber and basalt fiber are fully impregnated into the ball-milled material, and after the impregnation is completed, impregnated carbon fiber and impregnated carbon fiber are obtained; then the impregnated carbon fiber and the impregnated carbon fiber are three-dimensionally orthogonally woven, and after the weaving is completed, they are dried at 150°C to obtain a dry woven ceramic blank; finally, the dried woven ceramic blank is sintered at 800°C for 2.5 hours to obtain a high-toughness woven ceramic body.
[0098] Embodiment 3: A high-toughness braided ceramic material, comprising the following raw materials in parts by weight:
[0099] 37.5 parts of diopside, 25 parts of quartz, 12.5 parts of silicon carbide, 9 parts of boron nitride, 8 parts of modified carbon nanotube polyadmixture additive, 6 parts of intercalation synergist, 5 parts of aluminum oxide, 12.5 parts of water, and 4 parts of sodium dodecylbenzene sulfonate solution.
[0100] The mass fraction of the sodium dodecylbenzenesulfonate solution of the present embodiment is 3.5%.
[0101] The preparation method of the modified carbon nanotube polyadjusting additive of this embodiment is:
[0102] S01: placing the carbon nanotubes in a proton irradiation box for 12.5 min at an irradiation power of 375 W, then subjecting them to ultrasonic treatment in a sufficient amount of hydrochloric acid solution at an ultrasonic power of 475 W for 1 h, then subjecting them to washing, filtering, and drying to obtain pretreated carbon nanotubes;
[0103] S02: Add 3.5 parts of nano calcium carbonate and 2 parts of nano silica sol to 6.5 parts of lanthanum chloride solution, then add 3 parts of yttrium oxide and 1.5 parts of aluminum borate whisker, stir well, and obtain a polyadjusted doping solution;
[0104] S03: ball-milling the pretreated carbon nanotubes and the compounding doping liquid at a weight ratio of 5:3. After the ball-milling is completed, washing and drying are performed to obtain a modified carbon nanotube compounding doping agent.
[0105] The mass fraction of the hydrochloric acid solution in this embodiment is 3%; the mass fraction of the lanthanum chloride solution is 4.5%; the ball milling speed in S03 is 1250r / min, and the ball milling is 2h.
[0106] The preparation method of the intercalation synergist of this embodiment is as follows:
[0107] S101: adding 5 parts of flaky talc and 1.5 parts of silane coupling agent KH550 to 8 parts of chitosan solution by weight, and then adding 2.5 parts of carboxymethyl cellulose, stirring well, to obtain a modifier;
[0108] S102: stirring hydroxyapatite in a sufficient amount of 5% by mass sodium alginate solution to obtain hydroxyapatite liquid;
[0109] Adding 5.5 parts of a modifier to 12.5 parts of a hydroxyapatite liquid by weight, followed by ultrasonic treatment, and ending the ultrasonic treatment to obtain a modified liquid doped with hydroxyapatite;
[0110] S103: The modified liquid mixed with hydroxyapatite and the intercalation agent are mixed in a weight ratio of 3:5, and the mixture is ball-milled at a speed of 1500 r / min for 1 h. After the ball-milling is completed, the mixture is filtered and dried to obtain the intercalation synergistic agent.
[0111] The mass fraction of the chitosan solution in this embodiment is 3.5%; the ultrasonic power of the ultrasonic treatment is 475W, and the ultrasonic time is 35min.
[0112] The preparation method of the intercalant of this embodiment is:
[0113] The nano-bentonite was heat-treated at 235°C for 15 minutes, and then stirred and dispersed evenly in water at 5°C, and then filtered and dried to obtain the pre-treated nano-bentonite.
[0114] According to weight, 5.5 parts of pretreated nano bentonite and 2 parts of nano magnesium oxide were added to 6.5 parts of barium nitrate solution, and then 1.5 parts of nano titanium dioxide and 2.5 parts of sodium lignin sulfonate solution were added, stirred, filtered and dried to obtain an intercalation agent.
[0115] The mass fraction of the barium nitrate solution in this embodiment is 3%; the mass fraction of the sodium lignin sulfonate solution is 5.5%; the stirring speed of the stirring process is 500 r / min, and the stirring time is 35 min.
[0116] A method for preparing a high-toughness braided ceramic material of this embodiment includes the following steps:
[0117] Diopside, quartz, silicon carbide, boron nitride, modified carbon nanotube compound additives, intercalation synergist, alumina, water and sodium dodecylbenzene sulfonate solution are mixed and ball-milled at a ball-milling speed of 1000 r / min for 2 hours to obtain a high-toughness woven ceramic material.
[0118] A high-toughness braided ceramic body of this embodiment includes the following steps:
[0119] According to weight, 20 parts of high-toughness woven ceramic material are weighed, and then 5 parts of organic boron crosslinking agent CY-2, 3 parts of aluminum sol and 3 parts of polyacrylic acid are mixed and continued to be ball-milled to obtain ball-milled material; then carbon fiber and basalt fiber are fully impregnated into the ball-milled material, and after the impregnation is completed, impregnated carbon fiber and impregnated carbon fiber are obtained; then the impregnated carbon fiber and the impregnated carbon fiber are three-dimensionally orthogonally woven, and after the weaving is completed, they are dried at 150°C to obtain a dry woven ceramic blank; finally, the dried woven ceramic blank is sintered at 800°C for 2.5 hours to obtain a high-toughness woven ceramic body.
[0120] Comparative Example 1:
[0121] The difference from Example 3 is that no additive for modifying the carbon nanotubes is added.
[0122] Comparative Example 2:
[0123] The difference from Example 3 is that no pretreated carbon nanotubes are added in the preparation of the modified carbon nanotube compound additive.
[0124] Comparative Example 3:
[0125] The difference from Example 3 is that no multiplexing doping liquid is added in the preparation of the multiplexing doping agent for modified carbon nanotubes.
[0126] Comparative Example 4:
[0127] The difference from Example 3 is that no nano calcium carbonate or nano silica sol is added in the preparation of the multiplexed doping liquid.
[0128] Comparative Example 5:
[0129] The difference from Example 3 is that yttrium oxide and aluminum borate whiskers are not added in the preparation of the polyhydric doping solution.
[0130] Comparative Example 6:
[0131] The difference from Example 3 is that no intercalation synergist is added.
[0132] Comparative Example 7:
[0133] The difference from Example 3 is that no modified liquid mixed with hydroxyapatite is added in the preparation of the intercalation synergist.
[0134] Comparative Example 8:
[0135] The difference from Example 3 is that no hydroxyapatite liquid is added in the preparation of the modified liquid blended with hydroxyapatite.
[0136] Comparative Example 9:
[0137] The difference from Example 3 is that no modifier is added in the preparation of the modified liquid blended with hydroxyapatite.
[0138] Comparative Example 10:
[0139] The difference from Example 3 is that no flaky talcum powder or silane coupling agent KH550 is added to the modifier.
[0140] Comparative Example 11:
[0141] The difference from Example 3 is that no intercalating agent is added in the preparation of the intercalating synergist.
[0142] The fracture toughness of the woven ceramic bodies in Examples 1 to 3 and Comparative Examples 1 to 11 was tested. The products were scrubbed 50 times with a load of 10 N to test the scrubbing resistance. The products were placed under 3% and 7% hydrochloric acid mist conditions for 12 hours to test the hydrochloric acid corrosion resistance of 3% and 7%. The test results are shown in Table 1.
[0143] Table 1 Performance test results of the braided ceramic bodies in Examples 1 to 3 and Comparative Examples 1 to 11:
[0144]
[0145] It can be concluded from Examples 1 to 3 and Comparative Examples 1 to 11 that the product of Example 3 has excellent fracture toughness, and the product has excellent performance stability under the conditions of scrub resistance, 3% and 7% hydrochloric acid corrosion resistance, and the woven ceramic material has a significant effect of durable use;
[0146] It can be seen from Comparative Examples 1 to 11 and Example 3 that without adding the modified carbon nanotubes compounding additive and the intercalation synergist, the performance of the product is significantly reduced. The synergistic effect of the two is the most obvious.
[0147] The performance of the products tended to deteriorate when no pretreated carbon nanotubes, no compounding doping liquid, no nano-calcium carbonate, nano-silica sol, or yttrium oxide or aluminum borate whiskers were added to the compounding doping liquid in the preparation of the modified carbon nanotube compounding doping agent, and the performance of the products tended to deteriorate. The modified carbon nanotube compounding doping agent obtained by combining the compounding doping liquid obtained by the specific method of the present invention with the pretreated carbon nanotubes had the most significant performance effect.
[0148] In the preparation of the intercalation synergist, the modifying liquid doped with hydroxyapatite was not added, the hydroxyapatite liquid was not added in the preparation of the modifying liquid doped with hydroxyapatite, the modifier was not added in the preparation of the modifying liquid doped with hydroxyapatite, the flaky talc powder and the silane coupling agent KH550 were not added to the modifier, and the intercalation agent was not added in the preparation of the intercalation synergist. The performance of the products all showed a trend of deterioration to varying degrees. At the same time, the intercalation agent was not added in the preparation of the intercalation synergist, and the product performance deteriorated significantly. The intercalation synergist obtained by combining the modifying liquid doped with hydroxyapatite prepared by the modifier obtained by the specific method of the present invention with the intercalation agent had the most significant performance effect. The intercalation synergist obtained by replacing the intercalation synergist obtained by other methods was not as obvious as the effect of the present invention.
[0149] At the same time, the inventors of the present invention also found that the intercalant has a greater impact on product performance. Based on this, the present invention further explores the impact of the preparation of the intercalant on product performance.
[0150] Experimental Example 1:
[0151] The only difference from Example 3 is that no pretreated nano-bentonite is added in the preparation of the intercalant.
[0152] Experimental Example 2:
[0153] The only difference from Example 3 is that nano magnesium oxide is not added in the preparation of the intercalation agent.
[0154] Experimental Example 3:
[0155] The only difference from Example 3 is that no nano titanium dioxide is added in the preparation of the intercalant.
[0156] Experimental Example 4:
[0157] The only difference from Example 3 is that no barium nitrate solution is added during the preparation of the intercalant.
[0158] Experimental Example 5:
[0159] The only difference from Example 3 is that no sodium lignin sulfonate solution is added during the preparation of the intercalant.
[0160] The fracture toughness of the woven ceramic body in Experimental Examples 1 to 5 was tested. The product was scrubbed 50 times with a load of 10 N to test its scrubbing resistance. The product was placed in 3% and 7% hydrochloric acid mist for 12 hours to test its hydrochloric acid corrosion resistance stability at 3% and 7%. The test results are shown in Table 2.
[0161] Table 2 Performance test results of the braided ceramic body in Experimental Examples 1 to 5:
[0162]
[0163] It can be seen from Experimental Examples 1 to 5 that the performance of the product changes when no pretreated nano-bentonite is added in the preparation of the intercalation agent. Among the factors in the preparation of the intercalation agent, the performance deterioration is the most obvious, followed by the fact that no nano-titanium dioxide and nano-magnesium oxide are added in the preparation of the intercalation agent. The performance of the product also shows an obvious trend of deterioration. At the same time, no barium nitrate solution and no sodium lignin sulfonate solution are added in the preparation of the intercalation agent. The performance of the product has a trend of deterioration. The raw materials for the preparation of the intercalation agent are proprietary. Only the intercalation agent obtained by the specific method of the present invention has the most significant performance effect of the product. The use of other methods instead is not as significant as the effect of the present invention.
[0164] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0165] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A high-toughness braided ceramic material, characterized in that: It includes the following raw materials in parts by weight: 30-40 parts of diopside, 20-30 parts of quartz, 10-15 parts of silicon carbide, 7-11 parts of boron nitride, 6-10 parts of modified carbon nanotube polyadmixture additive, 5-7 parts of intercalation synergist, 4-6 parts of aluminum oxide, 10-15 parts of water, 3-5 parts of sodium dodecylbenzene sulfonate solution; The preparation method of the modified carbon nanotube polyadjusting additive is as follows: S01: placing the carbon nanotubes in a proton irradiation box for 10-15 minutes, with an irradiation power of 350-400W. After the irradiation is completed, ultrasonic treatment is performed in a sufficient amount of hydrochloric acid solution, with an ultrasonic power of 450-500W for 1 hour. After the ultrasonic treatment is completed, the carbon nanotubes are washed with water, filtered, and dried to obtain pretreated carbon nanotubes; S02: Add 2-5 parts of nano calcium carbonate and 1-3 parts of nano silica sol to 5-8 parts of lanthanum chloride solution by weight, then add 2-4 parts of yttrium oxide and 1-2 parts of aluminum borate whisker, stir well, and obtain a polyadjusted doping solution; S03: ball milling the pretreated carbon nanotubes and the compounding doping liquid at a weight ratio of 5:3, washing with water and drying to obtain a modified carbon nanotube compounding doping agent; The preparation method of the intercalation synergistic agent is as follows: S101: adding 4 to 6 parts of flaky talc and 1 to 2 parts of silane coupling agent KH550 to 6 to 10 parts of chitosan solution by weight, and then adding 2 to 3 parts of carboxymethyl cellulose, stirring well, to obtain a modifier; S102: stirring hydroxyapatite in a sufficient amount of 5% by mass sodium alginate solution to obtain hydroxyapatite liquid; Add 4 to 7 parts of a modifier by weight to 10 to 15 parts of a hydroxyapatite liquid, and then perform ultrasonic treatment until the ultrasonic treatment is terminated to obtain a modified liquid doped with hydroxyapatite; S103: mixing the modified liquid mixed with hydroxyapatite and the intercalation agent in a weight ratio of 3:5, and ball milling the mixture at a speed of 1500 r / min for 1 h. After the ball milling is completed, the mixture is filtered and dried to obtain an intercalation synergist. The preparation method of the intercalant is as follows: The nano-bentonite is heat-treated at 230-240°C for 10-20 minutes, then stirred and dispersed evenly in water at 5°C, then filtered and dried to obtain pre-treated nano-bentonite; According to weight, 4-7 parts of pretreated nano bentonite and 1-3 parts of nano magnesium oxide are added to 5-8 parts of barium nitrate solution, and then 1-2 parts of nano titanium dioxide and 2-3 parts of sodium lignin sulfonate solution are added, stirred, filtered and dried after the treatment is completed to obtain an intercalation agent.
2. A high-toughness woven ceramic material according to claim 1, characterized in that: The high-toughness braided ceramic material comprises the following raw materials in parts by weight: 37.5 parts of diopside, 25 parts of quartz, 12.5 parts of silicon carbide, 9 parts of boron nitride, 8 parts of modified carbon nanotube polyadmixture additive, 6 parts of intercalation synergist, 5 parts of aluminum oxide, 12.5 parts of water, and 4 parts of sodium dodecylbenzene sulfonate solution.
3. A high-toughness woven ceramic material according to claim 1, characterized in that: The mass fraction of the sodium dodecylbenzene sulfonate solution is 2-5%.
4. A high-toughness woven ceramic material according to claim 1, characterized in that: The mass fraction of the hydrochloric acid solution is 2-4%; the mass fraction of the lanthanum chloride solution is 3-6%; the ball milling speed of the ball milling treatment in S03 is 1000-1300 r / min, and the ball milling is for 2 hours.
5. A high-toughness woven ceramic material according to claim 1, characterized in that: The mass fraction of the chitosan solution is 2-5%; the ultrasonic power of the ultrasonic treatment is 450-500W, and the ultrasonic time is 30-40min.
6. A high-toughness woven ceramic material according to claim 1, characterized in that: The mass fraction of the barium nitrate solution is 2-4%; the mass fraction of the sodium lignin sulfonate solution is 4-7%; the stirring speed of the stirring treatment is 450-550 r / min, and the stirring time is 30-40 min.
7. A method for preparing a high-toughness woven ceramic material, used for preparing a high-toughness woven ceramic material as claimed in any one of claims 1 to 6, characterized in that: The following steps are involved: Diopside, quartz, silicon carbide, boron nitride, modified carbon nanotube compound additives, intercalation synergist, alumina, water and sodium dodecylbenzene sulfonate solution are mixed and ball-milled at a ball-milling speed of 1000 r / min for 2 hours to obtain a high-toughness woven ceramic material.
Citation Information
Patent Citations
Ceramic material processing technique
CN102745999A
Method for producing wall and floor tiles by slab scraps
CN102826828A